Free vibration characteristic analysis of functionally graded shells with porosity and neutral surface effects. (1st July 2022) - Thang, Pham Toan; Do, Dieu T.T.; Nguyen, Tan-Tien; Lee, Jaehong; Nguyen-Thoi, T.
Abstract: Thin cylindrical shells are widespread in structural engineering, such as civil engineering structures, oil rigs, oil pipes, rocket hull and aircraft fuselages. With the development of materials science, the behavior of the cylindrical shell structures made of advanced materials has attracted many scientists. This paper proposed an analytical approach through a closed-form solution for analyzing the free vibration characteristic of FG cylindrical thin and thick shells considering simultaneously the effect of porosities and the neutral surface. Both the classical shell theory (CST) and the shear deformation shell theory (SDST) are employed to establish governing equations for the free vibration problem. The natural frequencies of FG cylindrical shells with porosities are obtained by using the Navier solution. The results obtained from this study are confirmed by comparing with existing ones. In addition, the effects of the neutral surface, material parameter as well as mode vibration on the natural frequencies are examined. Highlights: A model of the FG cylindrical shell with porosities. The effect of the physical neutral surface is considered. An useful analytical solution is applied. This study focuses on obtaining the formulas of natural frequencies.